2022
DOI: 10.21203/rs.3.rs-1366911/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Perfectionism as a Predictor of Physician Burnout

Abstract: Burnout is common among physicians and has detrimental effects on patient care and physician health. Recent editorials call attention to maladaptive perfectionism in medicine and the potential role of perfectionism in physician burnout; however, no studies to date have examined the effect of perfectionism on burnout in physicians practicing in the United States. This study examined the unique effects of demographics, perfectionism and personality traits on burnout among physicians. This was a cross-sectional s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…This study marks the first instance where the relationship between perfectionism and burnout is elucidated from the perspective of a betrayal of values. The SEM results extend the findings of Martin et al 20 and Testoni et al 13 , underscoring the susceptibility to burnout exhibited by SPP physiotherapists when confronted with moral injury. SPP was not the only domain on the MPS-SF to have a relationship with burnout.…”
Section: Perfectionism Moral Injury and Burnout's Pathwaysupporting
confidence: 86%
See 4 more Smart Citations
“…This study marks the first instance where the relationship between perfectionism and burnout is elucidated from the perspective of a betrayal of values. The SEM results extend the findings of Martin et al 20 and Testoni et al 13 , underscoring the susceptibility to burnout exhibited by SPP physiotherapists when confronted with moral injury. SPP was not the only domain on the MPS-SF to have a relationship with burnout.…”
Section: Perfectionism Moral Injury and Burnout's Pathwaysupporting
confidence: 86%
“…Martin et al 20 found perfectionism to significantly predict emotional exhaustion (β = 0.55, p = <.001) and depersonalisation (β = 0.18, p = .006) in physicians, while Biggs, McKay and Shanmugam 21 showed SPP to be associated with burnout (β = 0.36 p = .001) in physiotherapy students, suggesting perfectionism renders the person vulnerable to burnout. Against this backdrop, we argue the tendency to achieve perfection in the workplace adversely affects performance, placing individuals at risk of burnout.…”
Section: Perfectionism Moral Injury and Burnoutmentioning
confidence: 99%
See 3 more Smart Citations